Optoelectronic and thermal properties of boron-bismuth compound - Daoud, Salah; Bioud, Nadhira; Labgaa, Noudjoud; Mezouar, Rabie (International Journal of Physical Research, 2014)
In the present work, we report ?rst principles calculations of the near-neighbor distance (bond length) and the average energy gap using the pseudopotential plane wave method, in the framework of the density functional theory (DFT) within the local density approximation (LDA) and the Hartwigzen-Goedecker-Hutter (HGH) scheme for the pseudopotential of Boron- Bismuth compound in its structure zincblende phase. The refractive index, the plasmon energy, the force constants, the lattice energy, the homopolar and heteropolar energies, the ionicity, the linear optical susceptibility, the hardness, the dielectric constants, the Debye temperature and the melting temperature are then predicted by mean of some simple emperical formulas. The results obtained are analyzed and compared with the available theoretical data of the literature Keywords: Optoelectronic and Thermal Properties, BBi Compound.